Perancangan dan Analisa UI/UX Aplikasi Mobile BankHijau Menggunakan User-Centered Design dan User Experience Questionnaire - Yogiswara, Yogiswara; Ratnasari, Chanifah Indah (Journal of Information System Research (JOSH), 2024)
Waste management is a critical issue that affects not only Indonesia, specifically Yogyakarta, but the entire world. Ngudi Barokah Waste Bank is one of the waste sorting centers located in Yogyakarta. Ngudi Barokah waste bank has difficulties in the recording process because it is still done manually using books. In order to contribute to overcoming this problem, the BankHijau mobile application was built, which facilitates recording at Ngudi Barokah Waste Bank. In its development, the design of the user interface (UI) and user experience (UX) of the BankHijau application used a User-Centered Design (UCD) approach to suit user needs. The following stages are implemented: comprehending the user context, ascertaining user requirements, designing solutions, and conducting testing. The User Experience Questionnaire (UEQ) is utilized for testing purposes due to its ability to gather a detailed and thorough understanding of the user experience (UX). Testing was conducted on 26 respondents, who provided positive feedback on all aspects. The UEQ benchmark study reveals that attractiveness (2,15), efficiency (1,95), dependability (2,15), and stimulation (2,11) exhibit excellent criteria, while perspicuity (1,98) and novelty (1,54) provide good criteria. It can be concluded that the design of the BankHijau application is above the average of other applications. The existence of this application is expected to indirectly lower the volume of waste in final disposal sites (TPA) and encourage recycling, hence contributing to positive changes in waste management and helping overall environmental sustainability.